Postural control adaptations to different visual conditions in dancers and non-dancers with chronic ankle instability - Hong, Eun Ji; Kang, Jiho; Jeon, Hyung Gyu; Lee, Sae Yong; Song, Kyeongtak (Frontiers in Sports and Active Living, 2025)
PurposeEven though dancers have good postural control ability, ankle sprain is the most common injury among dancers, developing into chronic ankle instability (CAI). While dancers rely on visual cues during stage and practice, it is unknown how dancers with CAI perform balance in different visual conditions. This study compares (1) static postural control between eyes open and closed, (2) visual reliance, and (3) dynamic postural control among dancers with CAI, uninjured dancers, non-dancers with CAI, and uninjured non-dancers.MethodsTen dancers with CAI, 10 uninjured dancers, 10 non-dancers with CAI, and 10 uninjured non-dancers. Participants performed single-leg standing with eyes open (EO) and eyes closed (EC) conditions. COP area, velocity in mediolateral (ML) and anteroposterior (AP), and resultant velocity were calculated. Visual reliance (% modulation) was calculated using the percent change in COP values between EO and EC conditions. Participants performed a drop vertical jump and maintained balance to assess the dynamic postural stability index. A two-way analysis of variance (group and CAI status) and Bonferroni post hoc test were used to compare static balance, visual reliance, and dynamic balance.ResultsA main effect of CAI status was observed in COP area (p = 0.014) and COP AP velocity (p = 0.013) during static balance in the EO condition. We also observed CAI status main effect in COP area (p = 0.014), COP AP velocity (p = 0.010), and COP resultant velocity (p = 0.034), and a group main effect in COP ML velocity (p = 0.034) in EC condition. We found interactions between group and CAI status in the visual reliance of COP resultant velocity (p = 0.048), as well as significant group (p < 0.001) and CAI status effect (p = 0.006). However, there were no significant differences in dynamic postural control (p > 0.05).ConclusionCAI patients demonstrated postural control deficits in static balance under both eyes open and closed conditions compared to uninjured controls. However, dancers exhibited higher visual reliance than non-dancers, and CAI showed greater visual dependence than uninjured controls. This finding shows dancers use visual information differently, resulting in higher balance abilities.